Redefining the concept of professionalism in nursing: an integrative review - Azemian Azadeh; Ebadi Abbas; Afshar Leila (Frontiers of Nursing, 2021)
In today's world with sweeping changes, nurses are responsible for providing high-quality and cost-benefit care, which would almost be impossible unless they achieve their high professional status. To date, no precise and comprehensive definition of professionalism in nursing has been evidently proposed. In fact, many of the previously proposed definitions are either complicated or ambiguous. Moreover, there is no consensus in the literature on an exhaustive definition for “a professional nurse.” The present study aimed to illustrate the concept of professionalism in nursing and identify its defining characteristics.